Análisis de uso del suelo a partir de las imágenes Landsat en el cantón el Empalme, provincia del Guayas, en el periodo 1998 – 2015 - Santi Ruiz, Narciza Alexandra (2018)
The analysis of satellite images is very important for the detection and monitoring of the elements that exist in the environment, so it has become a valuable tool for the evaluation of different components of the Earth's surface, such as the studies of multitemporal analysis where it allows to detect the changes of the use of the vegetal cover in certain periods of time, evidencing the natural resources. The purpose of this research was to analyze the land use changes in the corner of Empalme, province of Guayas, using the Landsat 5 images of the year 1998 and Landsat 8 of the year 2015 with the help of the ArcGIS, ENVI tools, within the processing of the satellite images, the SAVI, NDVI, NDMI spectral indexes were calculated, thus detecting the vegetation cover of the study area. In the supervised classification of the images, the geographical coordinates of the field phase were taken as a reference, 6 training classes were selected, obtaining as a result the classified images of the two periods, in such a way that a certain process was carried out to obtain 60 random points, in the classified image of 2015, and in this way evaluate the validation of the points with the Google Earth tool, in which the confusion matrix was obtained, indicating a Kappa coefficient of 75.05% evidencing an acceptable value, through the calculated indices, the statistical analysis of the coefficient of variance of a factor (ANOVA) was executed, indicating that the NDVI and SAVI index has statistically significant differences between the distribution groups and the NDMI index does not exist statistically significant difference, for the evaluation of the multitemporal analysis of the two periods, it was determined that certain classes of use inferred in other classes, it was observed that the kind of forest that had in the year 1998 has reduced for the year 2015 which resulted in the expansion of soils for different uses of agricultural crops. Keywords: Landsat images, spectral indexes, supervised classification, land use change, multitemporal analysis.